2012
DOI: 10.1016/j.jfs.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Capital regulation, risk-taking and monetary policy: A missing link in the transmission mechanism?

Abstract: a b s t r a c tFew areas of monetary economics have been studied as extensively as the transmission mechanism. The literature on this topic has evolved substantially over the years, following the waxing and waning of conceptual frameworks and the changing characteristics of the financial system. In this paper, taking as a starting point a brief overview of the extant work on the interaction between capital regulation, the business cycle and the transmission mechanism, we offer some broader reflections on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
277
1
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 980 publications
(356 citation statements)
references
References 161 publications
11
277
1
10
Order By: Relevance
“…Moreover, both innovations in the global monetary policy stance (MP) and risk factor disturbances (RF) deepened the U.S. trade imbalance since the early 2000s, while portfolio allocation shifts (PA) and terms of trade shocks (TT) had a partially offsetting effect. The worsening of Td determined by monetary policy shocks accords with the basic mechanism of the international risk-taking channel of monetary policy (Borio and Zhu 2012;Bruno and Shin 2015): over-expansionary U.S. monetary policy caused a contraction in perceived risk and funding costs, fuelling asset prices and the net worth of financial institutions, as well as their leverage and risk-taking attitude, resulting in capital inflows into the U.S. and depreciation of the US$.…”
Section: Global Imbalances Liquidity and Financial Marketsmentioning
confidence: 96%
“…Moreover, both innovations in the global monetary policy stance (MP) and risk factor disturbances (RF) deepened the U.S. trade imbalance since the early 2000s, while portfolio allocation shifts (PA) and terms of trade shocks (TT) had a partially offsetting effect. The worsening of Td determined by monetary policy shocks accords with the basic mechanism of the international risk-taking channel of monetary policy (Borio and Zhu 2012;Bruno and Shin 2015): over-expansionary U.S. monetary policy caused a contraction in perceived risk and funding costs, fuelling asset prices and the net worth of financial institutions, as well as their leverage and risk-taking attitude, resulting in capital inflows into the U.S. and depreciation of the US$.…”
Section: Global Imbalances Liquidity and Financial Marketsmentioning
confidence: 96%
“…They found that the "confidence risk channel" is able to explain large negative price moves in the absence of fundamental changes in macroeconomic variables. The importance of "risk perception" and its feedback on asset values is also present in Borio and Zhu (2012), who find that "the mutually reinforcing feedback between perceptions of value and risk, on the one hand, and financing constraints and "liquidity", on the other, has arguably become more prominent. Under some circumstances, it may therefore also contribute to amplifying business fluctuations more than in the past" (p. 248).…”
Section: Third Variable: the Level Of Trust And Confidencementioning
confidence: 98%
“…As described in Calvo (1998) and Forbes and Warnock (2012), an exogenous sudden slowdown in capital flows can cause large unexpected changes in relative prices such as depreciation of the domestic currency and collapse of asset prices. These developments can trigger a further reversal of capital flows, leading to sharp corrections in collateral values and a credit crunch (Borio & Zhu, 2012;Meissner, 2013).…”
Section: The Transmission Of Portfolio Flowsmentioning
confidence: 99%